2018
DOI: 10.1177/0194599818785157
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Trends in Head and Neck Surgery Outcomes

Abstract: Substantial improvement in postoperative morbidity and mortality has taken place in head and neck surgery over the past decades. Static complication rates in some procedures may reflect that the improvement of surgical techniques allow for the treatment of sicker patients. The trends seen in this study speak to the importance of probing further why high rates of complications are still seen in certain procedures and ensuring that effective treatment is balanced with limiting morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…In our study population, we demonstrated minimal complications including hematomas, seromas, infections, and ED visits, and none of these were associated with the drain removal process. These complication rates are in line with overall complication rates for these head and neck surgeries 14–16 . In the future, a case–control or randomized trial study would definitively confirm this.…”
Section: Discussionsupporting
confidence: 71%
“…In our study population, we demonstrated minimal complications including hematomas, seromas, infections, and ED visits, and none of these were associated with the drain removal process. These complication rates are in line with overall complication rates for these head and neck surgeries 14–16 . In the future, a case–control or randomized trial study would definitively confirm this.…”
Section: Discussionsupporting
confidence: 71%
“…Head and neck oncologic surgical procedures range from small local resections to extensive, surgeries such as neck dissection or pharyngolaryngoesophagectomy with many also necessitating reconstructive surgery. Postoperative morbidity, mortality and expected LOS is known to vary depending on the complexity of the procedure along with other factors such as tumor location, stage, and salvage surgery 3,4 . Unfortunately, it was not possible to evaluate and perform sensitivity analysis for specific head and neck cancers or surgeries using the available data which limits the conclusions that may be definitively drawn from this meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional clinical treatments for maxillofacial tumours include surgery, radiotherapy, and chemotherapy. Unfortunately, current clinical therapies are destructive to hosts, resulting in unsatisfactory therapeutic outcomes as follows: (1) Physiological dysfunction [10][11][12] , including issues with chewing, speech, swallowing, sucking, and breathing, owing to the lack of maxillofacial bone and radiation and chemotherapeutic drug damage; (2) Psychological damage resulting from the impairment of normal physiological functions and maxillofacial deformity 13,14 , which could lead to depression and misanthropy in patients; and (3) Frequent tumour recurrence due to cancer cells that survive surgery, inaccessibility of tumours during operations, unpredictable variation and constantly increasing drug resistance. Some novel methods, such as immunotherapy 15,16 , have shown strong potential, particularly biomaterial-mediated therapies (including targeted chemotherapy, magnetic-mediated hyperthermia (MMT), photodynamic therapy (PDT), and photothermal therapy (PTT)), which have demonstrated high anticancer efficiency, specific tumour targeting properties, excellent biocompatibility and low invasiveness.…”
Section: Introductionmentioning
confidence: 99%